THE BENEFITS OF JOURNAL WRITING IN EFL CLASSROOM - Nissa, Khairun (TELL - US JOURNAL, 2024)
Passive students are one of the challenges in English as a foreign language (EFL) classroom. Most of the EFL learners are able to understand the speakers but cannot speak much themselves. The conceivable teaching strategies are very crucial in order to assist the teachers to encourage the students to practice and be active in the classroom. This paper would like to elaborate the potential benefit of journal writing, especially in improving students’ speaking skill. Also, as a reference for Indonesian English teachers to guide the students to communicate confidently in English. To discover the advantages, the literature research methodology will be applied to explore the core concepts. The findings indicate that journal writing has several positive effects in improving students’ speaking skill in EFL classroom, though there are some challenges that teachers need to consider in applying this method. The implication of this research aims to increase the number of “active speaker” among English learners by promoting journal writing as learning tools in EFL context.